2016
DOI: 10.1016/j.cell.2016.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Networking in T Cell Memory

Abstract: T-lymphocytes show large changes in ATP demand and nutrient utilization, imposed by their different roles as T memory and T effector cells. Therefore, T cell remodeling represents a bioenergetic challenge to mitochondria. New work from Buck et al. links changes in mitochondrial shape to T cell fate choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
1
10
0
1
Order By: Relevance
“…significantly lower (P<0.01) NBDG uptake than CD62L-cells ( Figure 7D-E), supporting the memory-like behavior of these CD62L+ cells (33,41). To meet differing energy requirements, effector T cells activate mitochondrial fission and subsequent fragmentation, while memory T cells inhibit mitochondrial fission, leading to mitochondrial elongation (42,43). In line with these reported observations, T cells from ICVtreated mice maintained fused mitochondrial networks that appeared elongated, while T cells from IVtreated mice had punctate mitochondria ( Figure 7F).…”
Section: Low Glycolytic Activity Represents An Intrinsic Quality Of Csupporting
confidence: 57%
“…significantly lower (P<0.01) NBDG uptake than CD62L-cells ( Figure 7D-E), supporting the memory-like behavior of these CD62L+ cells (33,41). To meet differing energy requirements, effector T cells activate mitochondrial fission and subsequent fragmentation, while memory T cells inhibit mitochondrial fission, leading to mitochondrial elongation (42,43). In line with these reported observations, T cells from ICVtreated mice maintained fused mitochondrial networks that appeared elongated, while T cells from IVtreated mice had punctate mitochondria ( Figure 7F).…”
Section: Low Glycolytic Activity Represents An Intrinsic Quality Of Csupporting
confidence: 57%
“…Naive T cells have a lower proliferation rate and cellular respiration and decreased mitochondrial proteome when compared to activated T cells (Almeida et al, 2016;Buck et al, 2016;Liesa and Shirihai, 2016;Ron-Harel et al, 2016). T cell activation leads to several rounds of cell division, which require the biogenesis of mitochondrial proteins, including those encoded by mtDNA.…”
Section: Proliferating T Cells Depend On Functional Mitoribosomes To mentioning
confidence: 99%
“…The proper functioning of mitochondria in T cells is critical for their activation, differentiation, and function [19]. T cell plasticity is influenced by their metabolism and ATP demand, where mitochondrial morphology plays an important role [14]. Recent research has shown cellular metabolism critically influences T cell differentiation and function, and emerges as a key target for therapy in the treatment of autoimmune diseases, infections, and cancer [19].…”
Section: Discussionmentioning
confidence: 99%
“…Drp1, a main component of the mitochondrial fission machinery, is a major player in mitochondrial morphology and metabolism. Drp1 inhibition has been observed in T memory cells (T M ) where mitochondria are fused together and have an elongated form; conversely, effector T cells (T E ) have fragmented mitochondria due to an upregulation of Drp1 phosphorylation [14]. Further, Drp1-dependent mitochondrial fission correlates with an increase in ROS production, CD95L-dependent, activation-induced cell death (ACID), and cytokine production in T cells, and inhibition of Drp1 in PHA- or anti-CD3-stimulated T cells results in reduced ROS, ACID, and cytokine production [24].…”
Section: Discussionmentioning
confidence: 99%